Pengaruh Pendidikan Kesehatan terhadap Perilaku Keluarga Penderita TB dalam Upaya Penanggulangan TB Dewasa di Kabupaten ABC Sumatera Barat - Gusneli Gusneli (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Tuberculosis (TB) is an infectious disease that attacks the lungs and other organs caused by mycobacterium tuberculosis. Tuberculosis is one of the biggest contributors to death in the world. Various TB control efforts have been undertaken by the government but have not yet reached maximum results. In efforts to control TB, it takes the role of the family in caring for family members who suffer from TB. This study aims to determine the effect of health education on family behavior in TB prevention efforts in one district in West Sumatra. The sample of this study was the families of adult TB sufferers in Dharmasraya District who met the inclusion criteria of 30 people consisting of intervention and control groups. Data collection using a questionnaire. The results showed that there was an influence of health education on the family behavior of TB patients in efforts to overcome adult TB including pre-test knowledge (p value 0.044) and post test (p value 0.001), pre-test attitude (p value 0.325) and post test (p value 0.001 ), pre test (p value 0.348) and post test (p value 0.001). Health education can change family behavior in TB control efforts. It is hoped that further researchers will develop a family monitoring book for TB sufferers.